Implementasi Sistem Monitoring Smart Parking berbasis IoTmenggunakan LoRa dan SIM800L V2 - Laily Muntasiroh; Akhmad Ulum; Sabhan Kanata (Applied Information Technology and Computer Science (AICOMS), 2026)
Parking area management in campus environments remains a significant challenge in the transformation toward an efficient and integrated smart campus ecosystem. This study proposes the implementation of an Internet of Things (IoT)-based smart parking monitoring system that integrates long-range communication (LoRa) and the GSM SIM800L V2 module within a two-node architecture to address the limitations of local network infrastructure. The primary objectives of this research are to: (1) evaluate the reliability of the system in detecting and transmitting parking slot status in real time, (2) measure the average transmission delay of data from sensor nodes to the server, and (3) assess the stability of data delivery under various GSM network conditions. The system was implemented using a combination of infrared sensors and ESP32 microcontrollers, while ThingsBoard was utilized as a web-based visualization platform. Experimental results demonstrated an average transmission delay of less than 3 seconds and a data transmission success rate exceeding 90%, even under marginal network conditions. These findings confirm the effectiveness of the LoRa-GSM-based IoT architecture for small-scale parking monitoring applications. Furthermore, the proposed system has the potential to be extended into a fully integrated intelligent parking solution supporting reservation services, occupancy prediction, 4G network utilization, and interoperability with other IoT platforms.